Basics of Mechanical Ventilation - Poor, Hooman (Springer International Publishing, 2018)
This book is a practical and easily understandable guide for mechanical ventilation. With a focus on the basics, this text begins with a detailed account of the mechanisms of spontaneous breathing as a reference point to then describe how a ventilator actually works and how to effectively use it in practice. The text then details: the various modes of ventilation commonly used in clinical practice; patient-ventilator interactions and dyssynchrony; how to approach a patient on the ventilator with respiratory decompensation; the optimal ventilator management for common disease states like acute respiratory distress syndrome and obstructive lung disease; the process of ventilator weaning; and hemodynamic effects of mechanical ventilation. Written for medical students, residents, and practicing physicians in a variety of different specialties (including internal medicine, critical care, surgery and anesthesiology), this book will instruct readers on how to effectively manage a ventilator, as well as explain the underlying interactions between it and the critically ill patient.